Disease state changes and safety of long‐term donepezil hydrochloride administration in patients with Alzheimer's disease: interim results from the long‐term, large‐scale J‐GOLD study in Japan. Issue 2 (26th June 2015) - Arai, Heii; Sumitomo, Kenta; Sakata, Yukinori; Daidoji, Kasumi; Takase, Takao; Toyoda, Tetsumi
Abstract: Background: There have been very few long‐term studies involving a large study population; existing studies usually have no more than a few hundred patients with Alzheimer's disease. For these reasons, there are no detailed investigations regarding changes in activities of daily living evaluated by the Functional Assessment Staging Test (FAST). Methods: A long‐term, large‐scale observational study of donepezil hydrochloride (Aricept ® ; Eisai Co., Ltd, Tokyo, Japan) is currently in progress. Its objective is to investigate disease state changes associated with the long‐term administration of this drug and its safety in patients with Alzheimer's disease. In this report, data collected over a maximum of 24 months were compiled. Efficacy was assessed using FAST and a cognitive function test (Mini‐Mental State Examination or the Hasegawa's Dementia Scale‐Revised). Results: The percentages of patients whose FAST stage improved or remained the same compared to at the start of donepezil hydrochloride administration (baseline) were 91.1% at 6 months, 83.0% at 12 months, 79.5% at 18 months, and 74.8% at 24 months. Multivariate logistic regression analysis was conducted to investigate factors that affect the improvement and maintenance or exacerbation of FAST at 24 months. 'Independence level in the daily life of elderly with dementia' and 'duration of illness' were identified as variables that affected the improvement and maintenance or exacerbation of FAST. Cognitive function improved significantly at 12 weeks and at 6 months compared to baseline, maintained baseline levels at 12 months and at 18 months, and decreased significantly at 24 months compared to baseline. Conclusions: This is the largest prospective study involving Alzheimer's disease patients in Japan, and we believe it is an important study that shows the reality of daily clinical practice.